Management strategies based on the IAS21 premises that help with the decision-making process - Monasterio Pérez, Johnny; García La Marca, María Fernanda; Pérez, Katherine; Zabala, Herbert (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To propose management strategies based on the IAS21 approach for the decision-making process in a medium-sized economic entity located in the Bolivarian Republic of Venezuela. MATERIAL AND METHOD: The research was based on a field design with a descriptive level and a mixed approach (qualitative-quantitative). As a means of data collection, a semi-structured interview was applied to key informants who hold important positions in the entity, and a quantitative analysis was used that came from the documentation and review of financial statements. RESULTS: The results reveal that the current functional currency in the studied entity is the Bolivar, and consequently, it is the currency used in the financial statements, since it serves as the legal currency in Venezuela; however, the management analyzes its financial reports, cash flows, and the accounts of various creditors and clients, in a foreign currency, specifically in US dollars: which to date, differs from the one used to present its financial statements. CONCLUSIONS: Through internal factors (IAS21) and the interviews conducted, the need to change the functional currency to benefit the management decision-making process was confirmed.